PENGARUH METODE BERCERITA BUKU BERGAMBAR TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK TADIKA PURI PEKANBARU - Novita, Evlin; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : The effect of Picture Book Tells Methods Speech Against Children Aged 5-6 Years On Tk Tadika Castle Pekanbaru. Language plays a very important in a child's life, because through language the child can communicate with the surrounding environment, and expressing ideas or thoughts to others. Initial survey that has been done in kindergarten Tadika Castle Pekanbaru, children are still often mispronouncing words such as the word "this pencil whom" the child said "this pencil anyone", said the "big ball" is pronounced "big ball", the majority children may not be able to tell what it is doing in the morning before going to school with simple, there are still many children who have not been able to ask the right example "bu broom where?" that should be "bu where his broom?" and many children that one can not distinguish the words "earlier, yesterday, past and present. The purpose of this study was to determine the increase in the ability to speak with a child aged 5-6 Picture Book Tells method in kindergarten Tadika Puri Pekanbaru. This study design using experimental research with one group pretest posttest design. Population and sample were 20 children in group B TK Tadika Castle Pekanbaru. The data collection techniques used are direct observation techniques. Data analysis techniques used t-test. Results of comparative analysis between the pretest to posttest ability to speak the child at significant level of 0.05 was obtained thitung -14.165 and sig value of 0.000, it can be concluded learning method proved Picture Book Tells significantly affect the child's ability to speak. Kindergarten teachers are expected to be able to apply the method Tadika Castle Picture Book Tells in improving children's ability to speak and the liveliness of the child in learning activities. Key word : The effect of Picture Book Tells Methods, Speech Against Children Aged 5- 6 Years